Netherlands Journal of Geosciences - Netherlands Journal of Geosciences (Cambridge University Press, 2026)
Netherlands Journal of Geosciences - Geologie en Mijnbouw is a fully open access journal which publishes papers on all aspects of geoscience, providing they are of international interest and quality. The journal publishes new and significant research in geosciences with a regional focus on the Netherlands, the North Sea region and relevant adjacent areas. A wide range of topics within the geosciences are covered in the journal, including geology, physical geography, geophyics, (geo-)archeology, paleontology, hydro(geo)logy, hydrocarbon exploration, modelling and visualisation.
FI 0.51
Q3
Keywords: Earth; Space & Environmental Sciences; Geology & Geophysics; Acuerdos transformativos; Transformative agreements; Estratigrafía; Paleontología; Procesos sedimentarios; Geodinámica; Exploración de hidrocarburos